Risk factors of severe anemia among the pregnant women from an underprivileged rural area of northern India: a multivariate analysis - Mangla, Divya; Gole, Sheetal; Bansal, Nikhil; Yadav, Sushma; Kharolia, Ravinder; Singh, Abhishek (International Journal Of Community Medicine And Public Health, 2022)
Background: India serves as a home to 45.7% of anemic pregnant women (aged 15-49) with anemia of any grade during the course of their pregnancy. This study aims to estimate the prevalence of anemia and associated risk factors of severe anemia among pregnant women. Methods: Eligible antenatal women irrespective of period of gestation were screened for presence of anemia with help of hemoglobin (Hb) value at the time of admission. Typing of anemia was done. Detailed history was followed by physical examination. Univariate and multivariate analysis was done to study the risk factors of severe anemia among the study subjects. Results: Of total, 22.1% women were found to be severely anemic. Severely anemic women having residence in a rural area without road had odds more than twice (AOR=2.14) compared to severely anemic women having residence in a rural area connected with road (p=0.018). Similarly, severely anemic women aged <25 years (AOR=2.70), Illiterate (AOR=3.12), marriage age <18 years (AOR=2.33), having age at 1st pregnancy as <19 years (AOR=1.93), undergone ≤3 ANC visits (AOR=3.95). Anemic women with gravida score ≥4 had more than 4 times risk (AOR=4.15). Conclusions: The significant risk factors of severe anemia among pregnant women as observed in this study were having residence in a rural area without road, age <25 years, illiteracy of mother, marriage age (<18 years in completed years), age at 1st pregnancy as <19 years, ≤3 ANC visits, gravidity ≥4 and non-sanitary type toilet facility at home.